Logging in, coming out Open Table MCC's Community Connect as a safe space for queer Christians - Tolentino, Miryam Kalyxta Fontanilla; Brillon, Cherish Aileen A.; University of the Philippines Diliman College of Mass Communication (Quezon City University of the Philippines Diliman, 2024)
The Philippines, a predominantly Catholic country, remains entrenched in homophobic beliefs, leading to a significant gap in LGBTQIA+ rights. Limited spaces for self-expression, particularly within religious spaces, persist. Among these few spaces is Open Table Metropolitan Community Church, an LGBT-affirming church in the Philippines, with specific attention to Community Connect, its twice-monthly virtual service held on Zoom. This study aims to understand how queer Christians utilize and make sense of the virtual space, as well as its role in the resistance of the LGBTQIA+, especially within the context of religion. By employing participant observations across four (4) sessions of Community Connect and conducting interviews with five (5) participants, this research applies the combined concepts of resistance presented by Michel Foucault and the themes of cyberqueer studies outlined by Nina Wakeford. The findings indicate that, in addition to addressing accessibility concerns for Persons with Disabilities (PWD) and individuals who are not ‘out of the closet’, Zoom features afford participants various means to express themselves comfortably. Notably, Community Connect fosters a sense of safety in facilitating discussions that deepen self-awareness and promote understanding among the LGBTQIA+, serving as an entry point for queer Christians to actively take part in the fight for queer liberation.
Thesis
Includes bibliography
Keywords: LGBT community centers -- Philippines; Christian sexual minorities -- Philippines; Safe spaces -- Philippines